Investigation of the Absorption Spectrum of InAs Doping Superlattice Solar Cells - Peng, Ruiqin; Su, Wenkang; Yu, Zhiguo; Cao, Jiamu; Jiang, Dongwei; Wang, Dongbo; Jiao, Shujie (Nanomaterials (Basel, Switzerland), 2024)
InAs doping superlattice-based solar cells have great advantages in terms of the ability to generate clean energy in space or harsh environments. In this paper, multi-period InAs doping superlattice solar cells have been prepared.. Current density–voltage measurements were taken both in the dark and light, and the short-circuit current was estimated to be 19.06 mA/cm2. Efficiency improvements were achieved with a maximum one sun AM 1.5 G efficiency of 4.14%. Additionally, external quantum efficiency and photoluminescence with different temperature-dependent test results were taken experimentally. The corresponding absorption mechanisms were also investigated.